Social Exclusion and Poverty - Gideon Calder (The Routledge Handbook of Philosophy and Poverty, 2023)
Social exclusion is often addressed in conjunction with poverty, and this raises questions about the nature of each, and their relation to each other. This chapter explores some of those questions, with a particular focus what attention to social exclusion adds to what we would already be at stake within the boundaries of a broad understanding of poverty. As would be expected, answering that question depends largely on which particular versions of either term are adopted. After a general discussion of how the two terms align, the next section elaborates a distinction between resources- and relations-related factors in the analysis of social disadvantage. Because both aspects may feature more or less heavily in accounts of both poverty and social exclusion, it is a binary which helps situate issues and themes at stake in how the two terms relate. The third main section moves on to cover how resources and relations feature in recent debates about social justice in political philosophy – and seeks to draw some conclusions in turn about the extent to which priorities highlighted in the analysis of the social exclusion/poverty relationship can be addressed through a redistributive paradigm. The chapter concludes that when paired with that of poverty, the concept of social exclusion sheds extra, distinctive light in terms of the description and explanation of disadvantage – but that normatively speaking, it makes coherent sense to address the two together, and in terms of their inter-relations.